Structure solution and refinement of stacking‐faulted NiCl(OH). (3rd December 2015) - Bette, Sebastian; Dinnebier, Robert E.; Freyer, Daniela
Abstract : Two samples of pure NiCl(OH) were produced by hydrothermal synthesis and characterized by chemical analysis, IR spectroscopy, high‐resolution laboratory X‐ray powder diffraction and scanning electron microscopy. Layers composed of edge‐sharing distorted NiCl6 x (OH)6−6 x octahedra were identified as the main building blocks of the crystal structure. NiCl(OH) is isostructural to CoOOH and crystallizes in space group R m [ a = 3.2606 (1), c = 17.0062 (9) Å]. Each sample exhibits faults in the stacking pattern of the layers. Crystal intergrowth of ( A γ B )( B α C )( C β A ) and ( A γ B )( A γ B ) [C6 like, β‐Ni(OH)2 related] stacked layers was identified as the main feature of the microstructure of NiCl(OH) by DIFFaX simulations. A recursion routine for creating distinct stacking patterns of rigid‐body‐like layers in real space with distinct faults (global optimization) and a Rietveld‐compatible approach (local optimization) was realized and implemented in a macro for the program TOPAS for the first time. This routine enables a recursive creation of supercells containing ( A γ B )( B α C )( C β A ), ( A γ B )( A γ B ) and ( C β A )( B α C )( A γ B ) stacking patterns, according to user‐defined transition probabilities. Hence it is an enhancement of the few previously published Rietveld‐compatible approaches. This routine was applied successfully to create and adapt a detailed microstructure model to the measured data of two stacking‐faulted NiCl(OH) samples. The obtained microstructure models were supported by high‐resolution scanning electron microscopy images.